THE EFFECT OF APPLYING PLANTED QUESTION ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT OF NINETH GRADE OF SMP PABAKU STABAT - Freddy Wilamenggi; Conny M.Hum (Jurnal Serunai Bahasa Inggris, 2020)
The study is concerning with experimental study which discussed the effect of planted question technique on students’ achievement in writing narrative text. It took place at SMP Pabaku Stabat. The subjects were the nineth grade students with the population of 132 students. 60 students were chosen as the sample and group into experimental and control group. Each group consisted of 30 students. The experimental group was taught with planted question technique while the control one was taught without planted question technique. A writing test was used to collect the data on the students’ writing ability. The data collected were analyzed by using t-test. The result of the data analysis showed that the t-observed was 6,53. It was higher that the value of t-table (tt) is 1,67 for 5% and 2,39 for 1%. This meant that the alternative hypothesis (Ha) was accepted. It can be concluded that there is effect of planted question technique on students’ achievement in writing narrative text of nineth grade of SMP Pabaku Stabat.